Capacity retention behavior and morphology evolution of SixGe1−x nanoparticles as lithium-ion battery anode. (29th May 2015) - Ge, Mingyuan; Kim, Seongbeom; Nie, Anmin; Shahbazian-Yassar, Reza; Mecklenburg, Matthew; Lu, Yunhao; Fang, Xin; Shen, Chenfei; Rong, Jiepeng; Yi Park, Song; Suk Kim, Dong; Young Kim, Jin; et al.
Abstract: Engineering silicon into nanostructures has been a well-adopted strategy to improve the cyclic performance of silicon as a lithium-ion battery anode. Here, we show that the electrode performance can be further improved by alloying silicon with germanium. We have evaluated the electrode performance of Si x Ge1− x nanoparticles (NPs) with different compositions. Experimentally, Si x Ge1− x NPs with compositions approaching Si50 Ge50 are found to have better cyclic retention than both Si-rich and Ge-rich NPs. During the charge/discharge process, NP merging and Si-Ge homogenization are observed. In addition, a distinct morphology difference is observed after 100 cycles, which is believed to be responsible for the different capacity retention behavior. The present study on Si x Ge1− x alloy NPs sheds light on the development of Si-based electrode materials for stable operation in lithium-ion batteries (e.g., through a comprehensive design of material structure and chemical composition). The investigation of composition-dependent morphology evolution in the delithiated Li-SiGe ternary alloy also significantly broadens our understanding of dealloying in complex systems, and it is complementary to the well-established understanding of dealloying behavior in binary systems (e.g., Au-Ag alloys).